Experiences with the use of participatory approaches in highly pathogenic avian influenza (HPAI) surveillance - Jost, Christine; Bloland, P.; Busuulwa, M.; Munstermann, S.; Okuthe, S.; Parmley, J.; Pfeiffer, Dirk U.; Pissang, C.; Soumare, B.; Mariner, Jeffrey C. (International Livestock Research Institute, 2012)
Animal health surveillance needs to provide information for action. Veterinary Services (VS), particularly in developing countries, are often under-resourced in personnel and budget and thus lack frequent contact with livestock farmers. By emphasizing the importance of farmers’ knowledge and experience, participatory disease surveillance (PDS) is an approach that helps VS to address this gap. It is a process of learning and discovery that fosters better cooperation and understanding between veterinary professionals and farmers. It evolved in response to past failures with classical approaches. Practitioners of PDS rely on semi-structured interviews during which techniques that allow for visualization, scoring and direct observation are used to increase communication and understanding. Secondary sources of information and diagnostic testing provide critical additional information.